If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2079 = 2x + 2(2x + -5) + 5x + 10 Reorder the terms: 2079 = 2x + 2(-5 + 2x) + 5x + 10 2079 = 2x + (-5 * 2 + 2x * 2) + 5x + 10 2079 = 2x + (-10 + 4x) + 5x + 10 Reorder the terms: 2079 = -10 + 10 + 2x + 4x + 5x Combine like terms: -10 + 10 = 0 2079 = 0 + 2x + 4x + 5x 2079 = 2x + 4x + 5x Combine like terms: 2x + 4x = 6x 2079 = 6x + 5x Combine like terms: 6x + 5x = 11x 2079 = 11x Solving 2079 = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 2079 + -11x = 11x + -11x Combine like terms: 11x + -11x = 0 2079 + -11x = 0 Add '-2079' to each side of the equation. 2079 + -2079 + -11x = 0 + -2079 Combine like terms: 2079 + -2079 = 0 0 + -11x = 0 + -2079 -11x = 0 + -2079 Combine like terms: 0 + -2079 = -2079 -11x = -2079 Divide each side by '-11'. x = 189 Simplifying x = 189
| 3(1-a)=-a+5 | | -98=-28x+2x^2 | | 5(7+n)=37+7n | | 27t+1t=-8t | | 7z-4=13+z | | (a+2)(a-4)+10=(-a-2)(6-a) | | -9-x=-4 | | -5/20c=20 | | 5/5-5/11 | | w/w-3-2w/2w-3=w-5/2w^2-9w+9 | | (4+2x+3x^2+6x^3)-(-4+2x-3x^2+6x^3)= | | 10X+6=9X-5 | | 5-(-9)=-4 | | 7a+10=a | | 2580+2920+x=3000 | | 1/6y^2=-y-3/2 | | 5(5-5a)+7=32-5a | | 6x+36=6x+36 | | 11r^2+14r+104=0 | | 0.12x+0.4(x-4)=0.01(5x-4) | | 0.3n+2=8 | | 8a-(4-a)=5a-28 | | 6n-6(5-n)=36+n | | 11-2x=5x+x | | -9x+x=4-6 | | 2079=2x+2(2x-5)+2(5x+10) | | 2/3(-9) | | 44=20 | | 2.5x-7=4x+19 | | 8(v+4)=24+8v | | -6p=3p | | v+2/v-1=7/2 |